Impacts of combined or single supplementation of branched-chain amino acids on delayed onset muscle soreness and muscle damage following resistance exercise - Asjodi, Foad; Daryabeygi Khotbesara, Reza; Pourghassem Gargari, Bahram; Izadi, Azimeh (Progress in Nutrition, 2018)
The purpose of this investigation was to determine and compare the effects of leucine (Leu), valine (Val), isoleucine (Ilue), and combined branched chain amino acids (BCAA) supplementation, on markers of muscle damage following resistance exercise. It was hypothesized that supplementation would attenuate the levels of indirect muscle damage markers and muscle soreness following exercise-induced muscle damage, and facilitate the restoration of muscle function. A total of 50 untrained males were randomly divided into five groups; Leu (n = 10), Ilue (n = 10), Val (n = 10), BCAA (n = 10), and placebo (n = 10). The muscle damage protocol specific to non-athletes is used in the current study. A 500 ml of group-specific solution was given to each group in two time points, 30 minutes before and immediately after performing the exercise. Multivariate analysis showed significant time differences for LDH in all groups (p